Insulin Injection Site Dystrophic Calcification with Fat Necrosis: A Case Report of an Uncommon Adverse Effect - Ramdas, Sharad (Medknow Publications & Media Pvt Ltd, 2014)
We report a case of an uncommon adverse effect of insulin injection resulting in hard subcutaneous swelling in the lower abdomen of a 47-year-oldfemale with type 1 diabetes. Extensive dystrophic calcification and fat necrosis was revealed on histopathological examination.